Gender, power and management : a cross-cultural analysis of higher education - Bagilhole, Barbara; White, Kate (Palgrave Macmillan, 2011)
Women are now part of senior management in higher education (HE) to varying degrees in most countries and actively contribute to the vision and strategic direction of universities. This book attempts to analyse their impact and potential impact on both organisational growth and culture